Sex-Pairing Pheromones in Three Sympatric Neotropical Termite Species (Termitidae: Syntermitinae) - Dolejšová, Klára; Křivánek, Jan; Kalinová, Blanka; Hadravová, Romana; Kyjaková, Pavlína; Hanus, Robert (Journal of chemical ecology, 2018)
Termite colonies are almost always founded by a pair of winged dispersers, in spite of the high costs and low success rates inherent in independent colony foundation. The dispersal flights of imagoes from natal colonies are followed by mate search, mediated by sex-pairing pheromones. Here, we studied the chemistry of sex-pairing pheromones and the related aspects of mate search in winged imagoes of two facultatively parthenogenetic species, Embiratermes neotenicus and Silvestritermes minutus, and an additional species from the same subfamily, Silvestritermes heyeri. All three species are widespread in the Neotropics, including the rainforests of French Guiana. After the dispersal flight and spontaneous loss of wings, females expose their hypertrophied tergal glands situated under abdominal tergites VIII - X. The females are attractive to males and, upon direct contact, the two sexes form characteristic tandems. Chemical analyses indicated that the females secrete species-specific combinations of unbranched, unsaturated C12 primary alcohols from the tergal glands, (3Z,6Z,8E)-dodeca-3,6,8-trien-1-ol (approx. 200 pg per female) and (3Z)-dodec-3-enol (185 pg) in E. neotenicus, (3Z,6Z)-dodeca-3,6-dien-1-ol (3500 pg) in S. heyeri, and (3Z,6Z)-dodeca-3,6-dien-1-ol (300 pg) and (3Z)-dodec-3-enol (50 pg) in S. minutus. (3Z,6Z,8E)-Dodeca-3,6,8-trien-1-ol and (3Z,6Z)-dodeca-3,6-dien-1-ol act as major pheromone components in the respective species and mimic the function of female tergal gland extracts in electrophysiological and behavioral experiments. Biologically relevant amounts of the third compound, (3Z)-dodec-3-enol, elicited non-significant reactions in males of E. neotenicus and S. minutus, and slight synergistic effects in males of S. minutus when tested in combination with the major component.
Keywords: mikroextrakce na pevné fázi; Alcohols; sexuální lákadla; stereoizomerie; druhová specificita; Exocrine Glands; Sexual Behavior, Animal; Female; Sex Attractants; Embiratermes neotenicus; Isoptera; Tergal glands; zvířata; Silvestritermes minutus; Stereoisomerism; Syntermitinae; Silvestritermes heyeri; plynová chromatografie s hmotnostně spektrometrickou detekcí; ženské pohlaví; Male; Species Specificity; Sex-pairing pheromones; exokrinní žlázy; Animals; Gas Chromatography-Mass Spectrometry; mužské pohlaví; sexuální chování zvířat; Solid Phase Microextraction; alkoholy